Wiener weighted algebra of functions of infinitely many variables - Atamanyuk, L. (Carpathian Mathematical Publications, 2015)
In this article we consider a weighted Wiener type Banach algebra of functions of infinitely many variables. The main result is a description of the spectrum of this algebra.